Challenges, paradigm shift and theoretical underpinnings of learning advising in higher education: The case of an Australian university in Singapore (Journal of Applied Learning and Teaching, 2020)
Learning advisors are teaching professionals who play an important role in higher education. They exist in universities in order to help students achieve success in their studies and in their careers. However, learning advisors are faced with some key challenges. One issue is the seemingly vague and inferior position that they have in higher education. Another challenge includes the questions about where they belong and what key roles they perform. This paper responds to these challenges through the following propositions: (1) creating a unique and more nuanced understanding of learning advising by looking at an Australian university in Singapore, (2) making a stand that learning advisors constitute a duality of self or function, i.e., as an academic and as a professional, (3) explaining a paradigm shift in learning advising by embracing the humanistic and social constructivist ideologies, and (4) framing the role of learning advisors within key theoretical lenses that guide them in performing such roles in higher education. Examples of teaching practices are discussed by situating them within the key theoretical frameworks. This paper concludes that learning advisors are both academics (teachers) and professionals (e.g., learning resource developers) and teaching is at the core of what they do. Higher education institutions must become proactive in clarifying the misconceptions associated with learning advising and in breaking the labels associated with learning support that proliferate in the academe.